PENGARUH KETEPATAN KODIFIKASI DIAGNOSIS TERHADAP PELAPORAN RL 5.3 (DAFTAR 10 BESAR PENYAKIT RAWAT INAP) DI RUMAH SAKIT UMUM DAERAH AL-IHSAN BANDUNG - Elsa Iskandar (Jurnal Infokes, 2023)
This study aims to determine the effect of codification accuracy on reporting 5.3 (a list of the top 10 inpatient diseases) at Al-Ihsan Hospital Bandung. The research method used is a quantitative research methodology with a descriptive approach. Data collection techniques used are by means of observation, questionnaires, interviews, and literature studies. The sampling technique used the Proportional Stratified Random Sampling technique with 6 medical record officers as respondents.The results of the study found that the accuracy of codification of inpatients had an effect of 97% on the reporting of RL 5.3 (list of the top 10 inpatient diseases) at Al-Ihsan General Hospital Bandung. While the remaining 3% is influenced by other variables not examined by the author, and produces a very strong correlation between the two variables, which is equal to 0.963. The problems found in this study were: 1) The doctor's writings were illegible, 2) incomplete medical records of discharged patients kept in the nursing room.The suggestions given are: 1) It is better for the DPJP to write down the diagnosis in a complete and legible way, 2) it is better to carry out outreach, monitoring and evaluation regarding SOP.Key words : Codification of Diagnosis, Accuracy, Reporting of RL 5.3 (list of the top 10 inpatient diseases).